The novelty of newspapers Victorian fiction after the invention of the news - Rubery, Matthew (New York ; Oxford : Oxford University Press, 2009)
Focusing on five diverse narrative conventions: the shipping intelligence, personal advertisement, leading article, interview, and foreign correspondence, this work shows journalism's concrete influence on the novel in the Victorian era.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English fiction -- 19th century -- History and criticism; Newspapers in literature; Journalism and literature -- Great Britain -- History -- 19th century; British newspapers -- History -- 19th century; Press and politics -- Great Britain -- History -- 19th century